Understanding the association between Big Five and relational aggression: The mediating role of social goals and friendship jealousy. (1st July 2020) - Kokkinos, Constantinos M.; Kountouraki, Magdalini; Voulgaridou, Ioanna; Markos, Angelos
Highlights: Mediation models of relational aggression (RAgg) integrating personality, social goals, and affect were tested. RAgg was positively linked to the positive FFM traits, social dominance, popularity and friendship jealousy. Friendship jealousy mediated the effects of openness to experience and neuroticism on RAgg. Extraversion was associated with less RAgg through high intimacy. Social dominance mediated the negative link between agreeableness and RAgg. Abstract: This study examined whether social cognitive processes (social goals of dominance, popularity, intimacy), and affect (friendship jealousy) mediate the links between personality traits (Five Factor Model; FFM) and relational aggression (RAgg), in and non-clinical sample of 235 Greek adolescents. Results revealed that RAgg was positively linked to energy/extraversion, agreeableness, conscientiousness, and openness, while it was negatively associated with neuroticism/emotional instability. Further, positive associations emerged between RAgg and social dominance, popularity and friendship jealousy. Mediation models showed that friendship jealousy mediated the effects of openness to experience and neuroticism/emotional instability on RAgg. Further, high intimacy mediated the negative association between energy/extraversion and RAgg, while social dominance mediated the negative link between agreeableness and RAgg. The results replicate prior research, while practical and theoretical implications are discussed.